The first definitive carcharodontosaurid (Dinosauria: Theropoda) from Asia and the delayed ascent of tyrannosaurids. - Brusatte, S; Benson, R; Chure, D; Xu, X; Sullivan, C; Hone, D (2009)
Little is known about the evolution of large-bodied theropod dinosaurs during the Early to mid Cretaceous in Asia. Prior to this time, Asia was home to an endemic fauna of basal tetanurans, whereas terminal Cretaceous ecosystems were dominated by tyrannosaurids, but the intervening 60 million years left a sparse fossil record. Here, we redescribe the enigmatic large-bodied Chilantaisaurus maortuensis from the Turonian of Inner Mongolia, China. We refer this species to a new genus, Shaochilong, and analyze its systematic affinities. Although Shaochilong has previously been allied with several disparate theropod groups (Megalosauridae, Allosauridae, Tyrannosauroidea, Maniraptora), we find strong support for a derived carcharodontosaurid placement. As such, Shaochilong is the first unequivocal Asian member of Carcharodontosauridae, which was once thought to be restricted to Gondwana. The discovery of an Asian carcharodontosaurid indicates that this clade was cosmopolitan in the Early to mid Cretaceous and that Asian large-bodied theropod faunas were no longer endemic at this time. It may also suggest that the ascent of tyrannosaurids into the large-bodied dinosaurian predator niche was a late event that occurred towards the end of the Cretaceous, between the Turonian and the Campanian.